Colistin induced neurotoxicity with bulbar palsy. A case report and literature review - Mohamed Kamal Mansour; Ali Mohamed; Raju Raghunathan (IDCases)
Colistin, a polymyxin antibiotic, is increasingly used to manage infections caused by multidrug-resistant gram-negative bacteria. This case report documents the occurrence of colistin-induced neurotoxicity manifesting as bulbar palsy in a 38-year-old male with a complex medical history. The patient, presenting with septic shock secondary to a diabetic foot ulcer, was administered colistin and meropenem, leading to a progressive onset of neurological symptoms. The timely discontinuation of colistin resulted in the complete resolution of neurotoxicity.